Robotic surgery in gastrointestinal surgery: History, current status, and challenges - Yu Liu; Qingyang Feng; Jianmin Xu (Intelligent Surgery)
Robotic surgery has been a part of clinical practice for over 30 years, and in recent years, the continuous emergence of new robotic platforms and technologies has brought about both changes and challenges in the field of gastrointestinal surgery,. providing the possibility for more precise surgery and smaller trauma. The publication of high-quality clinical studies gradually confirms the advantages of robotic surgery in gastrointestinal surgery. Especially in the field of colorectal cancer, the publication of research such as REAL has confirmed that robotic radical resection for rectal cancer has better short-term outcomes than laparoscopy. Although robotic surgery still faces some challenges, such as economic costs and learning curves, the future prospects of robotic technology in colorectal surgery are highly promising.